Journal Impact Factor, Eigenfactor, Journal Influence and Article Influence - Chia-Lin Chang; Michael McAleer; Les Oxley (Tinbergen Institute, 2013)
This paper examines the practical usefulness of two new journal performance metrics, namely the Eigenfactor score, which may be interpreted as measuring “Journal Influence”, and the Article Influence score, using the Thomson Reuters ISI Web of Science (hereafter ISI) data for 2009 for the 200 most highly cited journals in each of the Sciences and Social Sciences, and compares them with two existing ISI metrics, namely Total Citations and the 5-year Impact Factor (5YIF) of a journal (including journal self citations). It is shown that the Sciences and Social Sciences are different in terms of the strength of the relationship of journal performance metrics, although the actual relationships are very similar. Moreover, the journal influence and article influence journal performance metrics are shown to be closely related empirically to the two existing ISI metrics, and hence add little in practical usefulness to what is already known. These empirical results are compared with existing results in the literature.
urn:NBN:nl:ui:15-1765/38221
Keywords: A12; 330; Journal performance metrics; Research assessment measures; Total citations; 5-year impact factor (5YIF); Eigenfactor; Journal and Article influence; Fachzeitschrift; Sozialwissenschaft; Bibliometrie; Welt